Assessment of Relationship between Non-alcoholic Fatty Liver Disease and LV Diastolic Dysfunction in Patients with Type 2 Diabetes Mellitus - Maryam Faramarzpour; Mohammadreza Mohammad Hosseiniazar; Laya Hooshmand Gharabagh (Caspian Journal of Internal Medicine)
Background: To date, the clinical implications of the long-lasting non-alcoholic fatty liver disease (NAFLD) such as the left ventricular diastolic dysfunction (LVDD) in the course of type 2 diabetes mellitus (T2DM) are yet to be determined. The main aim of this study was to investigate the correlation between NAFLD and early LVDD progression along with demographic characteristics. Methods: This cross-sectional study was performed on ninety consecutive diabetic outpatients referred to the endocrinology clinic. Demographic data were collected using a designed checklist. Ultrasound imaging was performed to assess the fatty liver condition. To assess LV diastolic function, echocardiography was performed, using a trans-thoracic tissue Doppler echocardiography. Results: The results showed that the majority of participants were females (61.1%). The fasting blood glucose (FBG, mg/dl) level was 174.65 ±51.1. Also, the mean body mass index (BMI) was 28.92±4.19, which was significantly associated with NAFLD. It has been also estimated that 76.7% and 81.1% of diabetic patients had NAFLD and simultaneous LVDD, respectively. However, the statistical results did not show a significant association between non-progressive NAFLD and LVDD (p<0.05). Conclusion: There was no correlation between NAFLD and LVDD progression. However, timely evaluation of LVDD in T2DM outpatients with NAFLD can strongly help to prevent possible cardiomyopathy in high-risk populations.